THE EFFECTIVENESS OF PROBLEM BASED LEARNING MODEL BASED ON ETHNOSCIENCE ON STUDENT’S CRITICAL THINKING SKILLS - Jihan Nisa Amini; Dedi Irwandi; Evi Sapinatul Bahriah (JCER (Journal of Chemistry Education Research), 2021)
Abstract. The purpose of this study was to determine the effectiveness of the problem-based learning model based on ethnoscience on students' critical thinking skills on colloidal material. Experiments were conducted on a sample of 36 experimental class students with an ethnoscience-based problem-based learning model and 36 experimental class students with a convention learning model. This research method is a quasi-experimental design with a nonequivalent control group design. The instruments used are essay tests and observation sheets. The results of this study indicate that the average posttest in the experimental class is 76.08, which is higher than the control class, which is 69.33. These results indicate that the use of ethnoscience-based learning problem-based learning models on colloidal material is effective in improving students' critical thinking skills compared to using conventional models.